Diseño del Sistema de Explotación del Bloque “Carmen” de la Concesión Minera Joya de Oriente II Código 501381, ubicado en la Provincia de Zamora Chinchipe, cantón Yantzaza. - Yaguachi Neira, Geder Lizbeth (2024)
This research was developed with the purpose of designing the exploitation system for gold in the "Carmen" block of the Joya del Oriente II mining concession, code 501381, located in the Zamora Chinchipe Province, Yantzaza canton. The research starts from the need to open another exploitation front within the mining concession, in a way that contemplates a geological identification that leads to the calculation of exploitable reserves in order to design an exploitation system according to the topography of the deposit, taking into account economic measures and safety in the operation. The choice of the exploitation system was developed based on the geological-mining and mining-technical characteristics of the deposit that, through the use of software such as ArcGis, Auto CAD and Recmin, the data obtained in the field phase were processed. This investigation began with the topographic delimitation of the "Carmen" block, followed by the geological characterization through the description of outcrops and calicatas. In addition, 2 SEVS lines were carried out to improve the description of the geological continuity of the block, which led to the delimitation of 3 mineral blocks of 22-, 36- and 49-meters depth, respectively. The reserve calculation was carried out using the profile and block methods, resulting in specific data for each of the blocks, with a total of 18164.5 grams of gold in a volume of 4077580.9 m^3. Subsequently, the geometric parameters of the exploitation were calculated and designed according to the topography of the area. Finally, a profitability analysis was performed for each of the mineral blocks, revealing that the first two initial blocks are not economically viable due to their low grades, while block 3 stands out as profitable for exploitation, since it covers the extraction costs of the first blocks. However, when comparing the investment that must be used to start up the project and the profitability generated at the end of the 4 years of life, it is determined that economically the open pit exploitation of the "Carmen" Block is not profitable since the profit is minimal. Keywords: geological-mining, mining-technical, exploitation system, reserves, topography, outcrops, calicatas.